Geological and site specific factors influencing earthquake hazard assessment for New Brunswick, Canada - Broster, B.; Burke, K. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2011)
ABSTRACT Seismic hazard studies by Earthquakes Canada place most of New Brunswick in the moderate part of the hazard range. Limitations are identified with the documented earthquake database suggesting that revisions are necessary for location and magnitude of some of the known historical earthquakes. In addition, the disturbance from a given event magnitude can be modified by local geological conditions and site specific factors. This is particularly true for New Brunswick, where many of the communities were settled along river valleys and coastal areas, which are under-lain by thick deposits of glacial and alluvial sediments that can amplify ground motion. The historical documentation and paleoseismic studies that identify seismic-generated disturbances are reviewed in this paper. Ground motion from both moderate (4 MN) local and large (> 5 MN) regional earthquakes represents a hazard at some locations and particularly those sites adjacent to steep slopes or sites underlain by thick surficial deposits. Amplification of ground motion would be expected at sites overlying low shear wave velocity zones typical of alluvial sediments. This may explain the larger shaking eﬀects experienced in the downtown area of Fredericton from distant earthquakes. Alteration of springs, rivers and groundwater supplies has happened as a result of earthquakes, although few eﬀects remain permanent. Reports of earthquake-generated tsunamis and lake seiches are rare for New Brunswick. Earthquake-induced rock falls occurred along some rock slopes during moderate earthquakes in 1855 and 1937, and a landslide occurred in marine sediments possibly triggered by a minor unrecorded local tremor in 1977. This study identifies the need for future paleoseismic research and microzonation studies for the major communities within the province.